US-Japan Trade Relations Amid the Globalization Crisis - V. G. Shvydko (Vestnik MGIMO-Universiteta)
Abstract: Relations between Japan and the United States have shown significant changes in recent years. Although the main attention has been focused on the strategic and military aspects of these relations, mutual trade and investment, related policies and regulation attract more of the attention of the political elites of the two countries.The tensions between the two countries on this issue have a long history. However, they greatly intensified since President D. Trump moved into the White House. The 2019 trade negotiations and the conclusion of a limited trade agreement between the two countries did not result in a comprehensive settlement of conflicting approaches and stands on specific issues. The rising confrontation between the United States and China amid the spread of novel coronavirus epidemic in early 2020 alleviated tensions over Japan-US trade issues by temporarily removing them from the focus of attention of the US presidential administration. Nevertheless, soon they will again become hot issues in the agenda of bilateral relations in the larger context of the US trade policy.In Japan, fears are growing that long-term shifts in the worldview and attitudes of the American political elite pose new threats and create new difficulties for realizing Japan's interests. Of greatest concern is the erosion in the mind of the US elites of the established commitment to further liberalize global and regional international trade and investment through multilateral agreements and institutions. Trump administration’s policy versus main trade partners has shifted towards working out and revising bilateral agreements designed to make American foreign trade more manageable and balanced, and it well may represent part of a long-term change and continue irrespective of the outcome of the US presidential election.The changes that have occurred in Japan-US relations regarding mutual economic ties confirm the general tendency of the international trade and investment system to become more fragmented, shifting from multilateral global and regional platforms to ad hoc agreements with clearly defined national goals and priorities.A possible change of political leadership in both countries will not change these processes, which reflect both the characteristic features of the world perception by national elites and the objective interests of influential business groups. At the same time, trade and investment policy is increasingly affected by non-economic factors, mostly “national security” considerations. This increases the role of diplomatic maneuvering and other levers and forms of influence in regulating trade and investment flows, and business environment for national and multinational companies.